SATIRICAL EXPRESSION TRANSLATION IN THE NOVEL “WAR CRY” BY WILBUR SMITH - Harahap, Annisah Inriani; Muhammad Khairi Armis (ELP (Journal of English Language Pedagogy), 2025)
This study investigates the translation of satirical expressions in War Cry, a novel by Wilbur Smith, and its Indonesian version published by Gramedia in 2017. Adopting a qualitative content analysis method, the research identifies, classifies, and analyzes satirical elements specifically irony, sarcasm, and parody using Keraf’s (2006) typology of satire and Molina and Albir’s (2002) framework of translation techniques. A total of 29 satirical expressions were identified from the source text and target text, with irony emerging as the most dominant form (51.72%). Literal translation was the most frequently used technique, especially in rendering irony, suggesting a preference for surface fidelity over functional equivalence. However, this tendency often risks diluting the rhetorical impact of satire, particularly when cultural or ideological nuances are essential. While some interpretive strategies such as amplification, discursive creation, and compensation were applied, their usage was relatively limited. The findings highlight the need for increased contextual sensitivity, rhetorical awareness, and cultural literacy in translating satire, especially when dealing with themes of power, colonialism, and ideological critique. Theoretically, this research contributes to the limited body of knowledge on satire translation in the Indonesian context. Practically, it offers guidance for translators, educators, and publishers to enhance the effectiveness and fidelity of satirical translation across languages and cultures.